Conspectus of Phytoconstituents and Pharmacological Activities of Barleria lupulina Lindl.: A Review - Banerjee, Sabyasachi; Banerjee, Subhasis; Jha, Gaurab K.; Bose, Sankhadip (Current Traditional Medicine, 2021)
Folk medicine system has served mankind as a remedy of several clinical conditions since antiquity. Abundance and diversity of synthetic medicaments eclipsed the implementation of traditional medicines for some time, but the adverse reactions of synthetic medicaments have shifted people to the traditional medicine system again to retrieve its position. Over a duration of time, advancement in research and technology on traditional medicine systems has attracted people to start believing in the safety aspects of natural products. This review illustrates the diverse pharmacological benefits of numerous phytoconstituents of a magical plant, Barleria lupulina Lindl., belonging to the family Acanthaceaec, native to East Africa (Mauritius), Eastern India, Bangladesh; apart from that, it is also cultured in some places like Sri Lanka. It is commonly known as hophead Philippine violet, Lal-tarokh, etc. Traditionally the plant leaves are utilized to medicate in snakebites, dog bites, swelling, boils, sexual disorder, cough, fever, body ache, eczema, itches, bleeding wounds and rheumatism. The other pharmacological properties include antibacterial, anti- inflammatory, antidiabetic, antiulcer, antimitotic, diuretic, saluretic, kaliuretic, antiarthritic, antiviral, psychopharmacological, anticancer, analgesic, antioxidant and immunomodulatory activity. Till date, diversified phytoconstituents have been isolated and structurally elucidated, in which saponins, glycosides, resins, steroids, phenolic compounds, alkaloids, tannins and flavonoids are the predominant ones. With this ample information, the herb can be considered for isolating biomarkers to develop new lead for making of novel drugs. In an attempt to illuminate the importance of B. lupulina, this review has been developed upon contemplating its traditional, morphological, ecological, phytochemical, and pharmacological studies.
Keywords: neuropharmacological